Emerging infections—an increasingly important topic: review by the Emerging Infections Task Force. (April 2018) - ,; Beeching, N.; Di Caro, A.; Gkrania-Klotsas, E.; Kantele, A.; Kohlmann, R.; Koopmans, M.; Lim, P.-L.; Markotic, A.; López-Vélez, R.; Poirel, L.; Rossen, J.W.A.; et al.
Abstract: Objectives: This paper review trends in emerging infections and the need for increased clinical and laboratory surveillance. Methods: Factors that contributed to the emergence of recent outbreaks have been reviewed. Known, major outbreaks over the past two decades were reviewed. Results: We identified at least four major drivers of emergent infections: (i) increasing density of the human population; (ii) stress from farmland expansion on the environment; (iii) globalization of the food market and manufacturing; (iv) environmental contamination. The factors creating new opportunities for emerging infections include: (i) population growth; (ii) spread in health care facilities; (iii) an ageing population; (iv) international travel; (v) changing and expanding vector habitats. Conclusions: Emerging infections are unpredictable. In this review we argue that to discover new trends in infectious diseases, the clinicians have to look for the unusual and unexpected and ensure proper diagnostics and that syndromic surveillance must be supported by highly specialized laboratory services. Mathematical modeling has not been able to predict outbreaks More emphasis on the biology of evolution is needed. EID rarely stands out as unusual, and the continuous pressure on health care budgets forces clinicians and laboratories to prioritize their diagnostic work-up to common and treatable conditions. The European Society for Infectious Diseases and Clinical Microbiology, ESCMID, has established an Emerging Infections Task Force, EITaF, to strengthen the activities of the society on emerging infections and ensure that emerging infections is included in differential diagnostic considerations in everyday clinical practice.